Do administrative roles affect professors' research?. Issue 1 (1st February 2019) - Zhao, Yuehua; Lou, Wen
ABSTRACT: This study quantitatively investigated whether the research performance of academic administrators (leaders) was affected by their administrative services. We examined the quantity of 111 professors' publications and citations in the Web of Science including 90 deans and 21 university presidents, from 26 universities. To compare the effect on their research performances by their administrative roles, we proposed four periods: the pre‐position period, the latest position period, the reference period, and the in‐position period. Statistical methods were applied and suggested that administrative services have strongly affected academic leaders' research performances.